Production of nanocellulose using controlled acid hydrolysis from large-scale production - Yurid, Fitra; Handayani, Aniek Sri; Maturbongs, F. D.; Irawan, Yan; Sampora, Yulianti; Septiyanti, Melati; Ramdani, Dadan; Supriadi, Edi; Khairatun Najwa, Mohd Amin; Septevani, Athanasia Amanda (Institute of Physics, 2023)
Nanocellulose is generally known as a versatile material, which is suitable for various applications due to its unique physicochemical properties, including light weight, ease of tunable surface functionalization, and excellent mechanical properties. This research aims to characterize and synthesize nanocellulose produced from acid hydrolysis of large-scaled micro-fibrillated cellulose (MFC) derived from oil palm empty fruit bunches by varying concentrations of H2SO4 from 20 to 35 v/v %. The obtained large-scaled MFC had a density of 1.01 kg/m3 and was dominantly composed of 71% cellulose. After acid hydrolysis of MFC, there were gradual changes in the colour of the obtained cellulose nanocrystals (CNC) dispersion from light white to a darker color with the increase of acid concentration, in which the over hydrolysis occurs at 35% of acid concentration. The use of 25-30% H2SO4 showed the optimum condition to avoid over-hydrolysis and resulted in bright white color of CNC dispersion with excellent stability at zeta potential value of -74.2±0.1 to -88.4±0.2 mV. It was supported by Fourier transform infrared (FTIR) due to the presence of negatively charged sulfonyl and hydroxyl groups upon CNC formation to offer excellent dispersion stability. Based on transmission electron microscope (TEM), rod-like shape CNC with a low aspect ratio of 11.8 at the dimension of 12.8 ± 6.7 nm in width and 151.9 ± 38.3 nm in length was successfully produced. Based on X-ray diffraction (XRD) analysis, the crystallinity of the sample was 76%.